2020
DOI: 10.1253/circj.cj-19-1144
|View full text |Cite
|
Sign up to set email alerts
|

Reconduction After Second-Generation Cryoballoon-Based Pulmonary Vein Isolation ― Impact of Different Ablation Strategies ―

Abstract: and fewer CB applications and demonstrated comparable clinical outcomes. 3,4 After identifying the time to PVI (time-to-effect, TTE) as an essential indicator for durability of PVI, latest ablation strategies implemented the individual TTE. 5 Reducing the ablation time, omitting the bonus-freeze cycle and implementing the TTE to recent protocols resulted in shorter procedure duration and reduced periprocedural complications without affecting clinical outcomes. 3 Nevertheless, data on the impact of different ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The FIRE AND ICE trial prospectively randomized 762 patients with drug‐refractory PAF to either RF‐ or CB‐based PVI and demonstrated the noninferiority of CB ablation with respect to efficacy and overall safety 2 . Recent studies focusing on CB2 ablation demonstrated a high rate of PVI (84%–90%) during the index freeze cycle, excellent 1‐ to 5‐year clinical outcomes even if “no‐bonus” freeze protocols or a shorter freeze cycle duration were applied, and a high rate of durable PVI as demonstrated in patients undergoing repeat procedures for recurrent atrial tachyarrhythmia after index CB2 ablation 4,24,27–30 . TTE‐based ablation protocols aim for a reduction in total energy transfer per PV, which in turn may contribute to an even better safety profile of CB‐based PVI as compared to protocols with fixed freeze cycle duration with or without bonus‐freeze 9,11,18,25,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The FIRE AND ICE trial prospectively randomized 762 patients with drug‐refractory PAF to either RF‐ or CB‐based PVI and demonstrated the noninferiority of CB ablation with respect to efficacy and overall safety 2 . Recent studies focusing on CB2 ablation demonstrated a high rate of PVI (84%–90%) during the index freeze cycle, excellent 1‐ to 5‐year clinical outcomes even if “no‐bonus” freeze protocols or a shorter freeze cycle duration were applied, and a high rate of durable PVI as demonstrated in patients undergoing repeat procedures for recurrent atrial tachyarrhythmia after index CB2 ablation 4,24,27–30 . TTE‐based ablation protocols aim for a reduction in total energy transfer per PV, which in turn may contribute to an even better safety profile of CB‐based PVI as compared to protocols with fixed freeze cycle duration with or without bonus‐freeze 9,11,18,25,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The detailed intraprocedural management has been described in previous studies from our center. 13,14 In brief, the procedure was performed in patients under deep sedation using midazolam, sufentanyl and propofol. Two ultrasound-guided right femoral vein punctures were performed and 2x 8F short sheaths were inserted.…”
Section: Intraprocedural Managementmentioning
confidence: 99%
“…17, 18 The detailed intraprocedural management utilizing AF-CB2 and AF-CB4 has been described in previous studies. 9, 13 The pop-out phenomenon was defined by the observation of a balloon dislodgement from the PV ostium after initializing the freezing process. This was evaluated by a second injection of contrast medium and fluoroscopy 5-10 s after initializing the freezing process.…”
Section: Cryoballoon-based Pvi: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…With patient numbers in the mentioned studies ranging from around 18 to 66, our study with 30 patients is comparable. A retrospective study by Heeger et al with 192 patients found no differences in reconduction rate per PV 22 . The different dosing protocols adopted in these studies may have accounted for differences in outcome.…”
Section: Discussionmentioning
confidence: 92%